Volatile Compounds And Antibacterial Activities Of The Methanol Extracts Of Soft Corals (Octocorallia) From Pulau Payar And Pulau Songsong - Marican, Hana Binte Abdul Wahab (2018)
Soft corals are important in the coral reef ecosystem, and are known to produce secondary metabolites. These compounds are different from those produced by terrestrial organisms, and may yield new sources of antimicrobial medicines. The aim of this study is to identify using morphological and chemical characteristics of soft corals harvested off Pulau Payar and Pulau Songsong, in the northern Straits of Malacca. Specimens were extracted 1:1 ratio of dichloromethane:methanol and analysed using fourier transform infra-red spectroscopy (FTIR) and gas chromatography mass spectrometry (GCMS). Following Clinical Laboratory Standard Institute (CLSI) protocols, the antibacterial activites of the crude extracts were measured using disk diffusion for the diameter of the inhibition zone, and using broth dilution method to find the minimum inhibition concentration (MIC) and minimum bacteriocidal concentration (MBC) measurements. Thirteen specimens were identified, coming from 7 suborders, 9 families and 11 genera. Out of the eighty-eight compounds identified, 2,4-bis(1,1-dimethylethyl)- phenol and n-hexadecanoic acid were detected in all 11 extracts. Fourty-seven were unique to one extract only. Examples of the types of compounds extracted include phenols, sterols, poly unsaturated fatty acids and vitamins. Out of twelve crude extracts tested, 50 percent of them showed inhibition for Staphylococcus aureus and methicillin-resistant Staphylococcus aureus (MRSA); and approximately 8 percent have showed inhibition for Enterococcus raffinosus. The extract from Sarcophyton trocheliophorum tested positive for bacteriocidal properties against MRSA, with an MBC measurement of 10mg/mL. Soft corals around the world, have been found to contain beneficial chemical compounds, however not much research has been done in this region. This study shows that soft coral extracts found in the Pulau Payar and Pulau Songsong do have secondary metabolites with potential and this potential can be harnessed for future pharmaceutical exploration.